Extended Perinatal Mortality Audit in a Rural Hospital in India - Torre Monmany, Núria; Astete, Joaquín Américo; Ramaiah, Dasarath; Suchitra, Jyothi; Krauel, Xavier; Fillol, Manolo; Balasubbaiah, Yadamala; Alarcón, Ana; Bassat, Quique (American Journal of Perinatology, 2021)
Objective The aim of the study is to describe the status of perinatal mortality (PM) in an Indian rural hospital.Study Design Retrospective analysis of data was compiled from PM meetings (April 2017 to December 2018) following “Making Every Baby Count: audit and review of stillbirths and neonatal deaths (ENAP or Every Newborn Action Plan).”Results The study includes 8,801 livebirths, 105 stillbirths (SBs); 74 antepartum stillbirths [ASBs], 22 intrapartum stillbirths [ISBs], and nine unknown timing stillbirths [USBs]), 39 neonatal deaths or NDs (perinatal death or PDs 144). The higher risks for ASBs were maternal age >34 years, previous history of death, and/or SBs. Almost half of the PDs could be related with antepartum complications. More than half of the ASB were related with preeclampsia/eclampsia and abruptio placentae; one-third of the ISB were related with preeclampsia/eclampsia and gestational hypertension, fetal growth restriction, and placental dysfunction. The main maternal conditions differed between PDs (p = 0.005). The main causes of the ND were infections, congenital malformations, complications of prematurity, intrapartum complications, and unknown. The stillbirth rate was 11.8/1,000 births, neonatal mortality rate 4.4/1,000 livebirths, and perinatal mortality rate 15.8/1,000 births.Conclusion This is the first study of its kind in Andhra Pradesh being the first step for the analysis and prevention of PM.Key Points
Keywords: ICD; perinatal mortality; perinatal death; stillbirth; neonatal mortality; cause of death; risk factors